1985
DOI: 10.1152/ajpgi.1985.248.1.g35
|View full text |Cite
|
Sign up to set email alerts
|

Gastric mucosal protection by chronic restraint: effects of vagotomy

Abstract: This study was performed to determine the effects of vagotomy on the gastric mucosal resistance to ethanol injury that develops in the rat in response to prolonged mild restraint. The resistance to ethanol injury up to 4 days after cessation of chronic mild restraint (CMR) was also examined. Intragastric administration of ethanol/acid to rats previously subjected to 10 days of CMR produced significantly (P less than 0.0001) less damage than to the mucosae of control rats. While previous exposure to CMR appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It is known that autonomic nervous system (ANS), one of the main components of stress, exerts a profound influence on heart rate and digestion (10). However, the precise role of each component of the ANS in the gastric ulcer after stress exposure remains unclear as conflicting mechanistic explanations have been provided (2,17,35). Arakawa et al (2) reported that excessive peripheral sympathetic activity plays an important role in the WRS model.…”
mentioning
confidence: 99%
“…It is known that autonomic nervous system (ANS), one of the main components of stress, exerts a profound influence on heart rate and digestion (10). However, the precise role of each component of the ANS in the gastric ulcer after stress exposure remains unclear as conflicting mechanistic explanations have been provided (2,17,35). Arakawa et al (2) reported that excessive peripheral sympathetic activity plays an important role in the WRS model.…”
mentioning
confidence: 99%
“…In addition, blockade of PG synthesis using peripheral injection of indomethacin, at a dose that did not alter the integrity of the gastric mucosa, abolished intracisternal or DMN injection of TRH‐ or RX 77368‐induced gastric protection against EtOH 25 , 26 , 28 , 29 . Similarly, low doses of kainic acid microinjected into the Rpa protected the gastric mucosa against EtOH injury through PG‐dependent pathways 3 (Fig. 1).…”
Section: Central Trh‐induced Vagal Cholinergic Gastric Protection Agamentioning
confidence: 81%
“…Earlier observations, based largely on the influence of vagotomy, indicate that the vagus plays a role in gastric protection in rats. In particular, vagal‐dependent mechanisms participate in the adaptive gastric protection induced by mild restraint or irritants (intragastric diluted alcohol or acid) followed by strong irritants (40–100% ethanol (EtOH) or 0.6–1 mol/L acid) 1 –5 . Evidence for central vagal gastric protective mechanisms was also demonstrated by acute ablation of the dorsal motor nucleus of the vagus (DMN) or vagotomy, which potentiated gastric lesion formation induced by EtOH 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The gastric surface epithelial cell damage in response to the 1-hr stress was found to be due to increased gastric contrac tions via vagal overactivity inasmuch as the cell damage did not occur in the rats pre treated with atropine or the antispasmodic agent papaverine (9). The common character istic of mild irritants in association with their adaptive mucosal protection is damage to the surface epithelium which has been demon strated by histochemistry (10)(11)(12) and gastric mucosal potential difference (12), and vagal innervation is essential for adaptive protection by mild chronic restraint stress (8). Therefore, we have considered that adaptive cytopro tection can be achieved by restraint and water-immersion stress, which is widely used to induce acute stress ulcers in rats.…”
Section: Abstract-wementioning
confidence: 99%